2009
DOI: 10.1161/atvbaha.109.190926
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Procoagulant Phosphatidylserine Exposure Relies on High Cytosolic Calcium Rather Than on Mitochondrial Depolarization

Abstract: Objective-Relationships between intracellular Ca 2ϩ concentration ([Ca 2ϩ ] cyt ) and apoptotic events, such as mitochondrial depolarization (⌬⌿m loss) and Bcl-2 and Bad phosphorylation, were analyzed in platelets and Jurkat cells in relation to rapid procoagulant phosphatidylserine (PS) exposure. Methods and Results-Platelets were stimulated with A23187, thapsigargin (TG) and thrombin plus convulxin (Thr/Cvx), andJurkat cells with ionomycin, in the presence or absence of cyclosporin A (CsA), a mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…108 The results demonstrated that-regardless of the loss of membrane mitochondrial permeability-PS exposure is triggered by a marked increase in cytosolic calcium ions concentrations. Challenging previous observations, these findings clearly indicate that PS exposure can occur even without loss of membrane mitochondrial permeability.…”
Section: Mitochondrial Permeability Transition Pore and Ps Exposurementioning
confidence: 89%
See 1 more Smart Citation
“…108 The results demonstrated that-regardless of the loss of membrane mitochondrial permeability-PS exposure is triggered by a marked increase in cytosolic calcium ions concentrations. Challenging previous observations, these findings clearly indicate that PS exposure can occur even without loss of membrane mitochondrial permeability.…”
Section: Mitochondrial Permeability Transition Pore and Ps Exposurementioning
confidence: 89%
“…99 Accordingly, PS exposure is triggered by a marked increase in cytosolic Ca 2ϩ concentrations in platelets regardless of a loss of membrane mitochondrial permeability. 108 In any case, cyclosporin A holds promise for the pharmacological modulation of MP shedding in the clinical setting of kidney transplantation because treatment with cyclosporin A results in an earlier reduction of endothelial-derived MPs levels than in patients treated with tacrolimus/mycophenolate. 110 The above evidence indicates that different molecular pathways (caspase-dependent mechanisms, increased mitochondria permeability, sustained increase in intracellular calcium ions) can mediate membrane lipid scrambling and ultimately lead to PS exposure.…”
Section: Toward a Pharmacological Control Of Ps Exposure And Microparmentioning
confidence: 99%
“…Effective inducers of the latter response are the combination of the glycoprotein VI agonist convulxin (Cvx) with thrombin (Thr), or otherwise Ca 2ϩ ionophores such as A23187 and ionomycin (16,17). Common to these agonists is that they induce a high and sustained rise in cytosolic Ca 2ϩ , which is considered to trigger the Ca 2ϩ -operated membrane protein, TMEM16F, which regulates the scrambling of phospholipids and exposure of PS (18,19).…”
mentioning
confidence: 99%
“…Studies by Arachiche et al confirmed that a high cytosolic Ca 2+ concentration is an independent inducer of platelet apoptosis. 41 The COX-1 inhibitor indomethacin increased the ΔΨ m change at 0ºC in the absence of P38MAPK blocker but not with SB203580 present. Thus, at low temperature indomethacin facilitates the accumulation of free AA.…”
Section: Discussionmentioning
confidence: 93%